Criteria for the correctness of familiar terms - Ryabchikov A.I.; Zagryadskaya O.V.; Chepakov E.M. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to substantiate the criteria for the correctness of familiar terms in the field of physical culture and sports. Methods and structure of the study. As a result of the analysis of popular names of directions, comparing them with direction indicators for movements in choreography, criteria for determining the directions of circles and circular movements used for more than one cycle of such movements were identified. Results and conclusions. Since 1938, domestic gymnastic terminology, in the course of its development, has acquired a clear structure, principles and rules. The practice of using terms shows that the problem of application is not only that popular figurative expressions are used instead of system terms. In the specialized literature on terminology, there are currently no clear rules for determining the direction of circular movements. The rules given in gymnastics textbooks for indicating the directions of arcuate movements are not always applicable to circles and circular movements. The popular names of the directions of these movements, which are accepted by the majority of teachers, coaches and lovers of physical education, do not have criteria for their justification. The authors proposed criteria for determining the directions of circular movements, as well as a new principle for determining circular movements and circles by body parts.